Persepsi Viewers Konten YouTube Noice Pada Tayangan "Berbeda Tapi Bersama" Sebagai Media Penyampaian Pesan - Anggrahini, Risma Ajeng; Sardjono, Herning Suryo; Kusumo Aji, Haryo (Solidaritas, 2024)
ABSTRACT The use of YouTube as a medium for conveying messages and as a medium for sharing video content creates various perceptions for those who access it. "Berbeda Tapi bersama" content show is one of the YouTube content in the Noice channel which contains Islamic preaching that is packaged in a modern and contemporary way, various backgrounds of life and religious differences can be discussed in this content. This research aims to find out how viewers' perceptions of the Berbeda Tapi Bersama content show as a medium for delivering messages. By using the theory of the process of perception by Alex Sobur, namely through the process of selection, interpretation and reaction. The method used in this research is qualitative, to understand a phenomenon that has been experienced by the research subject through interviews and documentation. The results of this study are viewers (informants) perceive positively, namely, the show can open a new view points towards others, generate a high sense of tolerance, and change a better mindset and also YouTube as a medium as a medium for delivering very informative messages, as an effective source of knowledge, means of entertainment and YouTube is a place to channel creativity. Keywords: perception, content impressions, YouTube.